A study on the problem packaging design of local traditional cookies case study: Biskut Kelapa Mama / Nur Syakira Mohd Rashid - Mohd Rashid, Nur Syakira (2018)
Packaging is one of important role in medium or platform to attract the target audiences in purchasing of the product. Its play a very big role and a great impact in this modern era globalization which is people are more attracted with visual image in terms of marketing communication. However, nowadays local traditional cookies packaging are not having a good development in the aspect of material and design used. Whereas, the packaging design has become one of the most important and popular in the preferences of consumer purchases of manufactured products. The packaging design of local traditional cookies has no innovative revolution and development. The purpose of this study was to determine the importance of packaging design in promoting local traditional cookies. The study will focus on the elements of designing on local packaging cookies which will be the main attraction for consumer on the display of shelves market. This study will focus one of the Malay traditional cookies which is popular among the Malays. “Biskut Kelapa Mama” is the Malay traditional cookies that will be focusing on since it is more well known among Malays. To achieve the goals of the study, quantitative and qualitative research strategy is employed. According to Pearlfisher's creative partner and creator-headed Karen Welman (designweek.co.uk), crucially, each designer deserves to develop and transform a traditional sustainable design from which it deserves to be appropriate and able to attract users to change perceptions and which is primarily brand behavior and consumer choice.